KUALITAS LAYANAN PERPUSTAKAAN MENGGUNAKAN METODE LIBQUAL DI SMP NEGERI 18 KOTA JAMBI - Mahendra, Mutiara Annisa’; Nabila, Jeihan (Scinary, 2024)
The objective of this research is to describe the quality of library services using the LibQual Method at SMP Negeri 18 Kota Jambi. This study employs a quantitative research type with a descriptive method through the distribution of questionnaires as the data source. The population in this study consists of students at SMP Negeri 18 Kota Jambi, totaling 746 individuals. The sample was drawn using the simple random sampling technique, resulting in a sample size of 88 individuals. The results of the data analysis on service quality using the LibQual method at the library of SMP Negeri 18 Kota Jambi indicate that in the dimension of Affect of Service, the average score obtained was 3.06, which falls into the moderate category with an interval scale of 2.51-3.25. In this dimension, the quality of library services is good, but there is a need for improvement in librarian training and information control. In the dimension of Information Control, the average score obtained was 2.63, which also falls into the moderate category with an interval scale of 2.51-3.25. In this dimension, the quality of library services is good, but improvements are needed in the ease with which users can find the library materials they need. In the dimension of Library As Place, the average score obtained was 3.26, which falls into the moderate category with an interval scale of 2.51-3.25. In this dimension, the quality of library services in terms of the library room atmosphere is high, but there is also a need for improvement in room optimization and interior design to enhance the user experience and meet their needs more effectively. This effort is expected to create a more quality and engaging library service for library users